2011
DOI: 10.1093/jxb/err078
|View full text |Cite
|
Sign up to set email alerts
|

NO synthase-generated NO acts downstream of auxin in regulating Fe-deficiency-induced root branching that enhances Fe-deficiency tolerance in tomato plants

Abstract: In response to Fe-deficiency, various dicots increase their root branching which contributes to the enhancement of ferric-chelate reductase activity. Whether this Fe-deficiency-induced response eventually enhances the ability of the plant to tolerate Fe-deficiency or not is still unclear and evidence is also scarce about the signals triggering it. In this study, it was found that the SPAD-chlorophyll meter values of newly developed leaves of four tomato (Solanum lycocarpum) lines, namely line227/1 and Roza and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
68
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 39 publications
6
68
1
Order By: Relevance
“…S8). The result is consistent with previous reports (Chen et al, 2010b;Jin et al, 2011). Application of 2 mM Suc further increased the GUS staining in roots of Fe-deficient plants.…”
Section: Suc-modulated Fe Deficiency Responses Depend On the Auxin Sisupporting
confidence: 93%
See 3 more Smart Citations
“…S8). The result is consistent with previous reports (Chen et al, 2010b;Jin et al, 2011). Application of 2 mM Suc further increased the GUS staining in roots of Fe-deficient plants.…”
Section: Suc-modulated Fe Deficiency Responses Depend On the Auxin Sisupporting
confidence: 93%
“…Since previous studies have shown that auxins play a critical role in the regulation of Fe deficiency responses (Chen et al, 2010b;Jin et al, 2011;Wu et al, 2012b), it is therefore necessary to clarify whether auxins have an association with Suc in the regulation of Fe deficiency responses. As shown in Figure 9, in the presence of the auxin transport inhibitor NPA, the stimulating effect of Suc on root FCR activity and expression of IRT1, FRO2, and FIT in Fedeficient Col-0 plants were completely terminated.…”
Section: Suc-modulated Fe Deficiency Responses Depend On the Auxin Simentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have investigated plant responses to elevated CO 2 on the ecosystem, community, population, physiological and molecular scales. [1][2][3][4] Based previous studies, we reported that elevated CO 2 promoted the development of LRs of tomato and NO was a signaling molecule that controls these processes. 5 Increased LRs could eliminate nutrient stress under elevated CO 2 , which play an important role in nutrient acquisition.…”
mentioning
confidence: 99%